2018
DOI: 10.1159/000487450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mst1 on Endometriosis Apoptosis and Migration: Role of Drp1-Related Mitochondrial Fission and Parkin-Required Mitophagy

Abstract: Background/Aims: Mitochondrial homeostasis is implicated in the development and progression of endometriosis through poorly defined mechanisms. Mst1 is the major growth suppressor related to cancer migration, apoptosis and proliferation. However, whether Mst1 is involved in endometriosis apoptosis and migration via regulating the mitochondrial function remains to be elucidated. Methods: Expression of Mst1 in endometriosis was examined via western blots. Cellular apoptosis was detected via MTT and TUNEL assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 60 publications
(67 reference statements)
6
40
0
Order By: Relevance
“…However, the upstream regulatory molecule for Mff-required mitochondrial fission in the setting of DN remains unknown. In response to mitochondrial fission, mitochondria could employ lysosomes via Parkin to degrade damaged mitochondria and maintain a healthy mitochondrial population, which is essential for cell survival [18][19][20]. Notably, the impairment of Parkin-mediated mitophagy is a feature of DN, and various pharmacological activators of mitophagy have been shown to protect against glomerulosclerosis and proteinuria, renal hypertrophy, and mesangial expansion in rodent DN models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the upstream regulatory molecule for Mff-required mitochondrial fission in the setting of DN remains unknown. In response to mitochondrial fission, mitochondria could employ lysosomes via Parkin to degrade damaged mitochondria and maintain a healthy mitochondrial population, which is essential for cell survival [18][19][20]. Notably, the impairment of Parkin-mediated mitophagy is a feature of DN, and various pharmacological activators of mitophagy have been shown to protect against glomerulosclerosis and proteinuria, renal hypertrophy, and mesangial expansion in rodent DN models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian STE20-like kinase 1 (Mst1) is an element of the Hippo pathway, which was initially identified as a major growth suppressor that interrupts stem cell growth, proliferation and apoptosis ( 3 ). Subsequent studies have illustrated that Mst1 is also involved in sustaining cardiomyocyte survival in diabetic cardiomyopathy ( 4 , 5 ), suppressing endometrial stromal cell migration in endometriosis ( 6 ) and promoting cancer cell apoptosis in colorectal carcinoma ( 7 ). These findings indicated that Mst1 functions as a tumor suppressor by modulating cancer cell apoptosis, migration and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, various pathways seem to be involved in the pathological process of different diseases. For example, in the models of cardiac ischemia reperfusion injury [ 32 ] and endometriosis metastasis [ 33 ], the JNK-Mff pathway is activated and contributes to the augmentation of mitochondrial fission and cardiomyocyte death. In contrast, in cerebral ischemia reperfusion injury and hyperglycemia-mediated renal damage, mitochondrial fission is primarily activated by the ROCK1-Drp1 pathways [ 31 ].…”
Section: Introductionmentioning
confidence: 99%